Ag/Ag2O confined visible-light driven catalyst for highly efficient selective hydrogenation of nitroarenes in pure water medium at room temperature - Yin, Zhengliang; Xie, Liangxu; Cao, Shunsheng; Xiao, Yingguan; Chen, Gang; Jiang, Ying; Wei, Wenxian; Wu, Limin (Elsevier, 2020)
Although photocatalysis has attracted tremendous research interest, there still remains critical challenges (e.g., low visible-light quantum efficiency, organic media, etc.), especially for selective hydrogenation of nitroarenes. Herein, we design and synthesize the first confined photocatalyst by introducing the nanospace of double-shelled hollow silica sphere as a photocatalytic nanoreactor to promote the hydrogenation reaction with the fast reaction kinetics. This photocatalyst exhibits excellent activity, selectivity, and recyclability. Especially, superior selectivity (>99%) is achieved when used for the hydrogenation of nitroarenes under visible-light irradiation in pure water medium. Both experimental and theoretical simulation results indicate that the Ag/Ag2O structure and confined nanospace of the photocatalyst greatly increase the contact probability between photogenerated atomic hydrogen and nitroarenes. Additionally, corresponding anilines are obtained almost quantitatively towards the hydrogenation of nitroarenes in pure water medium at room temperature. Therefore, this work provides a rational design concept of highly efficient visible-light photocatalyst for green chemistry industry.
Keywords: Photocatalytic nanoreactor; Nitroarenes; Confinement effect; Visible-light irradiation; Superior selectivity